Neoecological component of higher environmental education in Ukraine - Сафранов, Т. А.; Некос, А. Н. (Man and Environment. Issues of Neoecology, 2014)
We consider the essence of the concept of  «neoecology» and neoecological component of higher environmental education in Ukraine. The new details of neoecology are considered, there are objective, subject, basic key concepts, issues of complexity and interdisciplinarity of neoecology. The article describes point of view which concerns elaboration of the structural units and structural-logic content of neoecology and also constant development of neoecology as science or academic discipline designed for the preparation of environmental specialists.